Numerical Modelling of Air Flow Attributes in a Contractions Chamber - Michalcová Vladimíra; Kuznětsov Sergej; Pospíšil Stanislav (Transactions of the VŠB: Technical University of Ostrava, Civil Engineering Series, 2014)
The article describes air flow turbulent attributes in the enclosed chamber of a rectangular cross-section contraction for the purpose of confirming its optimal shape. The task is solved numerically using Ansys Fluent software. Right models were selected based on the evaluated results at a contraction's outlet which were compared to the physics experiment